Early Restrictive Fluid Strategy Impairs the Diaphragm Force in Lambs with Acute Respiratory Distress Syndrome. (23rd March 2022) - Ijland, Marloes M.; Ingelse, Saranke A.; van Loon, Lex M.; van Erp, Merijn; Kusters, Benno; Ottenheijm, Coen A. C.; Kox, Matthijs; van der Hoeven, Johannes G.; Heunks, Leo M. A.; Lemson, Joris
Abstract : Background: The effect of fluid management strategies in critical illness–associated diaphragm weakness are unknown. This study hypothesized that a liberal fluid strategy induces diaphragm muscle fiber edema, leading to reduction in diaphragmatic force generation in the early phase of experimental pediatric acute respiratory distress syndrome in lambs. Methods: Nineteen mechanically ventilated female lambs (2 to 6 weeks old) with experimental pediatric acute respiratory distress syndrome were randomized to either a strict restrictive fluid strategy with norepinephrine or a liberal fluid strategy. The fluid strategies were maintained throughout a 6-h period of mechanical ventilation. Transdiaphragmatic pressure was measured under different levels of positive end-expiratory pressure (between 5 and 20 cm H2 O). Furthermore, diaphragmatic microcirculation, histology, inflammation, and oxidative stress were studied. Results: Transdiaphragmatic pressures decreased more in the restrictive group (–9.6 cm H2 O [95% CI, –14.4 to –4.8]) compared to the liberal group (–0.8 cm H2 O [95% CI, –5.8 to 4.3]) during the application of 5 cm H2 O positive end-expiratory pressure ( P = 0.016) and during the application of 10 cm H2 O positive end-expiratory pressure (–10.3 cm H2 O [95% CI, –15.2 to –5.4] vs . –2.8 cm H2 O [95% CI, –8.0 to 2.3]; P = 0.041). In addition, diaphragmatic microvessel density was decreased in the restrictive group compared to the liberal group (34.0 crossings [25th to 75th percentile, 22.0 to 42.0] vs. 46.0 [25th to 75th percentile, 43.5 to 54.0]; P = 0.015). The application of positive end-expiratory pressure itself decreased the diaphragmatic force generation in a dose-related way; increasing positive end-expiratory pressure from 5 to 20 cm H2 O reduced transdiaphragmatic pressures with 27.3% (17.3 cm H2 O [95% CI, 14.0 to 20.5] at positive end-expiratory pressure 5 cm H2 O vs. 12.6 cm H2 O [95% CI, 9.2 to 15.9] at positive end-expiratory pressure 20 cm H2 O; P < 0.0001). The diaphragmatic histology, markers for inflammation, and oxidative stress were similar between the groups. Conclusions: Early fluid restriction decreases the force-generating capacity of the diaphragm and diaphragmatic microcirculation in the acute phase of pediatric acute respiratory distress syndrome. In addition, the application of positive end-expiratory pressure decreases the force-generating capacity of the diaphragm in a dose-related way. These observations provide new insights into the mechanisms of critical illness–associated diaphragm weakness. Abstract : Using an ovine model of pediatric acute respiratory distress syndrome with lung-protective ventilation, the authors compared a strict restrictive fluid strategy with norepinephrine to a liberal fluid strategy over a 6-h period evaluating transdiaphragmatic pressure over a wide range of positive end-expiratory pressure levels along with evaluation of diaphragm microcirculation, histology, and biomarkers reflective of inflammation and oxidative stress. Baseline measurements of transdiaphragmatic pressures before lung injury showed an inverse relationship with increasing positive end-expiratory pressure. Fluid restriction significantly reduced transdiaphragmatic pressures at positive end-expiratory pressure levels of 5 and 10 cm H2 O but not at 15 or 20 cm H2 O. Microvessel density was significantly reduced, although the histology and markers of inflammation and oxidative stress were not affected.